Pengaruh Solvabilitas Dan Ukuran Perusahaan Terhadap Return Saham Dengan Profitabilitas Sebagai Variabel Intervening Pada Perusahaan Sektor Kesehatan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2021 - Dwi Yudiono; Angga Negoro, Dhimas; Bertuah, Eka (Jurnal Ilmiah Ekonomi Global Masa Kini, 2024)
This study aims to examine and analyze the effect of solvency ratios and company size on stock returns by using profitability as an intervening variable in health sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period. Using a quantitative descriptive approach, the population in this study were 21 companies belonging to the health sector (IDXHealth) on the Indonesia Stock Exchange. With purposive sampling, the final sample used is 16 companies. Observations were carried out for 3 years in a quarterly period so that 16 companies were multiplied by 12 quarterly periods so that 192 observations were obtained. After the data in the study were collected, then data analysis was carried out using statistical software tools consisting of descriptive analysis methods, correlation tests, regression tests, classical assumption tests, model tests and direct and indirect effect tests/intervening tests. The results showed that solvency has an effect on profitability, while firm size has no effect on profitability. Meanwhile testing the model on factors that affect stock returns, GLS (Generalized Least Square) is a fit model. The test results show that profitability affects stock returns and profitability can mediate solvency, but cannot mediate firm size on stock returns. Keywords : Solvency, Profitability, Firm Size, Stock Returns